The noisy foxes - Husband, Amy (Woodbridge : Top That, 2014)
"In a very noisy house in a very noisy city lived three noisy foxes. The foxes decide that it would be nice to be quite sometimes and set off to find a new home. They soon discover that finding the perfect place to live is not that easy!"--Cover.
Keywords: Children's stories